Membrane translocases in a mitochondrially derived organelle: a study of the T. vaginalis hydrogenosome - Kay, Christopher (2012)
Eukaryote cells are the products of a complex history of interspecies interactions, with some organelles now known to have arisen through the endosymbiosis of prokaryotic cells. Whilst these organelles 'evolved' from the original endosymbionts, their evolution has not stopped within the modern eukaryote. Trichomonas vaginalis is protozoan parasite, with an unusual cellular biology, this species appears to lack peroxisomes, and instead of mitochondria has divergent organelles called hydrogenosomes.